(untitled) (Revista Crioula, 2008)
ONE OF THE EÇA DE QUEIRÓS’S FAVORITE STRATEGIES IN HIS JOURNALISTIC TEXTS IN THE 1890S WAS THE USE OF DRAMA AS METAPHOR IN THE REFLECTION ON THE EUROPEAN REALITY. IN THE ARTICLE "A ESPANHA", PUBLISHED IN THE GAZETA DE NOTÍCIAS IN 1894, EÇA NARRATES AN ANARCHIST ATTACK, IN A FARCE FORMAT, BY AIMING TO DENOUNCE IRONICALLY THE IDEOLOGICAL CHARACTER OF THE ANARCHIST TERRORISM.